Integrating Project-Based Collaborative Learning into English Classroom: A Systematic Review - Putimasurai, Putimasurai; Angraini, Desti; Mukhlash Abrar; Sulistiyo, Urip (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This paper systematically reviews the integration of Project-Based Collaborative Learning (PBCL) in English classrooms, focusing on the aims, methodologies, results, novelty, and contributions of studies conducted over the past decade. The review identifies key patterns, gaps, and future research opportunities in PBCL, offering insights for educators and policymakers. The findings highlight the effectiveness of PBCL in improving student engagement, language acquisition, and collaborative skills, making a compelling case for its wider adoption in English language classroom education.